Dynamically shaping the surface of silica colloids. Issue 40 (4th October 2022) - Niggel, Vincent; Hsu, Chiao-Peng; Isa, Lucio
Abstract : The shaping of the surface of silica particles obtained from the reaction of two silane precursors is highly dynamical and affects the final particle roughness. Abstract : Surface roughness is an important design parameter to influence the processing of particle-based materials. Current methods to synthesize rough particles present some limitations, e.g . low yield, relative methodological complexity, requirements of multiple steps, or poor roughness control. Here, we thoroughly investigate a facile synthesis route where two silanes, tetraethyl orthosilicate (TEOS) and vinyltrimethoxysilane (VTMS), are added in one pot to form silica particles with controlled corrugated surfaces. We first show that the morphology of these particles can be defined by regulating the amount and ratio of the two silane precursors and by adjusting the concentration of ammonia during synthesis. We characterize the surface topography of the particles using atomic force microscopy and show a direct correlation between surface roughness and the synthesis conditions. Furthermore, we carry out an in situ observation of the evolution of surface morphology and propose a mechanism for surface structuring that hinges on the formation of silane droplets, followed by the preferential hydrolysis/condensation reaction of VTMS starting from the droplet surface and evolving towards the center. The exchange of liquid from the droplets through the VTMS shell leads to stress accumulation and wrinkling/buckling of the particles. Moreover, we explicitly show that osmotic imbalances between the inside and the outside of the droplets regulate their shrinking. We therefore demonstrate that exchanging solvents has a comparable impact to adjusting silane and ammonia content in defining the particle shape and that this synthesis route is highly dynamical. Finally, we demonstrate that it is possible to incorporate fluorescent dyes during synthesis to enable future studies on the impact of surface roughness on dynamic processes, including shear, via direct high-resolution imaging. Our findings show that the mechanism for wrinkling and buckling in colloidal silica particles follows a general scheme found in a broad range of systems, from liposomes and polymeric capsules to Pickering emulsion droplets.